Legal Certainty on Licensing and Royalty Mechanisms in Public Performances in the Form of Music Concerts Following the Constitutional Court's Decision - Melawati Widyafitri; Miranda Risang Ayu Palar; Tasya Safiranita Ramli (Journal of Law, Politic and Humanities, 2026)
The use of musical works in public performances in the form of music concerts frequently gives rise to disputes among composers, performers, and event organizers within the music concert industry ecosystem. Legal uncertainty concerning licensing mechanisms and royalty payments for the explotation of the economic rights in music concerts constitutes one of the underlying factors contributing to legal disputes arising after the performance has taken place. The Constitutional Court Decisions Number 28/PUU-XXIII/2025 and Number 37/PUU-XXIII/2025, rendered in the context of judicial review of Copyright Law Number 28 of 2014, provide a constitutional interpretation of the regulation governing the use of musical works in public performance. However, in practice, these decisions continue to leave room for legal uncertainty, particularly concerning the timing of licence fulfilment and the obligation to pay royalties. This study adopts a normative juridical method, employing statutory and conceptual approaches. The findings of the study indicate that, following the Constitutional Court decisions, further regulatory measures are to specifically govern the mechanism of obtaining licences and paying royalties in public performance in the form of music concerts. In addition, preventive measures legal violations may be implemented through a clear contractual arrangements in cooperation agreements between performers and event organizers, particularly concerning obligations related to licence fulfilment and royalty payments, in order to ensure legal certainty, the protection of economic rights, and a balanced framework for all parties involved.